Nuclear receptors constitutive androstane receptor and pregnane X receptor ameliorate cholestatic liver injury - Stedman, Catherine A. M. (National Academy of Sciences, 2005)
Cholestasis is associated with accumulation of bile acids and lipids, and liver injury. The constitutive androstane receptor (CAR) and pregnane X receptor (PXR) are xenobiotic nuclear receptors that coordinate protective hepatic responses to potentially toxic stimuli, including bile acids. We investigated the role of these receptors in the regulation of bile acid and lipid metabolism in a bile duct ligation (BDL) model of cholestasis applied to receptor knockout mice. Hepatic damage from bile acid accumulation was increased in both CAR knockout (CARKO) and PXR knockout mice, but bile acid concentrations were lower in CARKO mice. High-density lipoprotein (HDL) cholesterol was elevated in CARKO mice, and serum total cholesterol increased less in CARKO or PXR knockout mice than WT mice after BDL. Gene expression analysis of the BDL knockout animals demonstrated that, in response to cholestasis, PXR and CAR both repressed and induced the specific hepatic membrane transporters Oatp-c (organic anion transporting polypeptide C) and Oatp2 (Na(+)-dependent organic anion transporter 2), respectively. Induction of the xenobiotic transporter multidrug resistance protein 1 in cholestasis was independent of either PXR or CAR, in contrast to the known pattern of induction of multidrug resistance protein 1 by xenobiotics. These results demonstrate that CAR and PXR influence cholesterol metabolism and bile acid synthesis, as well as multiple detoxification pathways, and suggest their potential role as therapeutic targets for the treatment of cholestasis and lipid disorders.